2000
DOI: 10.1139/y99-123
|View full text |Cite
|
Sign up to set email alerts
|

PYY preference is a common characteristic of neuropeptide Y receptors expressed in human, rat, and mouse gastrointestinal epithelia

Abstract: This investigation describes the relative potencies of four peptide agonists, namely, peptide YY (PYY), [Leu3l,Pro34]PYY (Pro34pYY), neuropeptide Y (NPY), and [Leu31,Pro34]NPY (Pro34NPY), as antisecretory agents in human, rat, and mouse gastrointestinal preparations. The inhibition of agonist responses by the Y1-receptor antagonist BIBP 3226 was also tested in each preparation. An unexpectedly pronounced preference for PYY and Pro34PYY was observed in functional studies of two human epithelial lines stably tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…1B) might reflect internalized receptors due to tonic internalization in the absence of agonist, as recently suggested [13]. Cells expressing Y 1 Δ32 receptors were incubated at 4°C, a condition which fully inhibits Y 1 receptor internalization due to the temperature dependence of the internalization process [21].…”
Section: Agonist-independent Internalization Of Y 1 δ32 Receptorsmentioning
confidence: 88%
See 3 more Smart Citations
“…1B) might reflect internalized receptors due to tonic internalization in the absence of agonist, as recently suggested [13]. Cells expressing Y 1 Δ32 receptors were incubated at 4°C, a condition which fully inhibits Y 1 receptor internalization due to the temperature dependence of the internalization process [21].…”
Section: Agonist-independent Internalization Of Y 1 δ32 Receptorsmentioning
confidence: 88%
“…Arrestins then serve as scaffold proteins by binding directly to the AP-2 complex and the clathrin necessary for coat formation. Recent studies have determined which serine and threonine are necessary for β-arrestins binding to the Y 1 C-terminus receptor in response to agonist activation [13,14,32]. This stretch of serine/threonine is located distally compared to the YETI motif (see Table 1) and is thus absent in the Y 1 Δ32 and Y 1 Δ42 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory effects on cAMP production (Servin et al, 1989) and electrolyte secretion (Laburthe et al, 1982;Voisin et al, 1990;Eto et al, 1997) in intestine were also shown to be PYY-preferring with PYY being more potent than NPY. The PYY preference has recently been claimed as being a common characteristics of receptors in gastrointestinal epithelia (Holliday et al, 2000). Although characterized at the biochemical level as a 44-kDa glycoprotein (Voisin et al, 1991), the intestinal PYY receptor has not been yet cloned.…”
mentioning
confidence: 99%